FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Wardatul Janah; Tatik Zulaika; Leliana Maria Angela (AKUNTANSI DEWANTARA, 2023)
Abstract. The purpose of this study was to analyze the effect of prudence, operating cycle, gender diversity and default risk partially and simultaneously on earnings quality. This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange from 2018-2020 with purposive sampling method. The sample of this study consisted of 125 companies with a total of 375 observations. The method used in this study was a statistical analysis method whose calculations were carried out using SPSS version 25. The statistical tests used were descriptive statistical analysis, classical assumption test, multiple linear regression analysis, partial test (statistical t test), simultaneous test (statistical F test), and coefficient of determination test (R2). Based on the results of the partial test, prudence has a significant negative effect on earnings quality and operating cycle, and a significant positive effect on earnings quality. While gender diversity and default risk partially have no significant effect on earnings quality. Simultaneous test results show that prudence, operating cycle gender diversity and default risk together have a significant effect on earnings quality. Keywords: prudence, operating cycle, gender diversity, default risk, and earnings quality